Driver Behavior in Utilizing Rest Areas for Fatigue Mitigation on the Bakauheni–Terbanggi Besar Toll Road - Teguh Suryono; Diana Nur Afni (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2026)
Driver fatigue remains one of the leading factors contributing to road traffic accidents, particularly in long-distance freight transportation. Rest areas are provided as supporting facilities to reduce fatigue; however, their effectiveness depends largely on drivers' utilization behavior. This study aimed to analyze the behavior of freight transportation drivers in utilizing rest areas as a fatigue mitigation strategy at Rest Area KM 49A on the Bakauheni–Terbanggi Besar Toll Road, Lampung. A quantitative approach with a descriptive analytical design was employed. Data were collected through observations, questionnaires, interviews, and documentation involving 100 freight drivers selected using accidental sampling. The data were analyzed using validity and reliability tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results indicate that driver behavior and rest area utilization simultaneously have a significant effect on fatigue mitigation, while rest area utilization provides a greater contribution than driver behavior. Limited parking capacity and inadequate supporting facilities were identified as the main barriers to optimal utilization. The findings emphasize the importance of improving rest area facilities to enhance driver safety and reduce fatigue-related traffic accident risks.